Art Therapy Experiential Workshops During Work Hours to Promote Doctors’ Wellbeing – A Quantitative Analysis - Safia Zaffarullah; Claire O’Donoghue; Richard Whitaker (BJPsych Open)
Aims: Risk of burnout amongst Resident Doctors is higher now than even pandemic levels with 63% of trainees at moderate-high risk in the 2024 GMC NTS. With an ever-increasing need to consider novel approaches to tackle this, Art Therapy (AT) “experiential” workshops were delivered for attendees of the weekly academic programme at SABP NHS Foundation Trust.